The Diagnosis and Treatment of Heel Pain: A Clinical Practice Guideline–Revision 2010 - Thomas, James L.; Christensen, Jeffrey C.; Kravitz, Steven R.; Mendicino, Robert W.; Schuberth, John M.; Vanore, John V.; Weil, Lowell Scott; Zlotoff, Howard J.; Bouché, Richard; Baker, Jeffrey (The Journal of foot and ankle surgery, 2010)
Heel pain, whether plantar or posterior, is predominantly a mechanical pathology although an array of diverse pathologies including neurologic, arthritic, traumatic, neoplastic, infectious, or vascular etiologies must be considered. This clinical practice guideline (CPG) is a revision of the original 2001 document developed by the American College of Foot and Ankle Surgeons (ACFAS) heel pain committee.